Closing the gap: connecting sudden representational change to the subjective Aha! experience in insightful problem solving - Danek, Amory H.; Williams, Joshua; Wiley, Jennifer (Psychological research, 2020)
Two hallmarks of insightful problem solving are thought to be suddenness in the emergence of solution due to changes in problem representation, and the subjective Aha! experience. Although a number of studies have explored the Aha! experience, few studies have attempted to measure representational change. Following the lead of Durso et al. (Psychol Sci 5(2):94-97, 1994) and Cushen and Wiley (Conscious Cognit 21(3):1166-1175, 2012), in this study, participants made importance-to-solution ratings throughout their solution attempts as a way to assess representational change. Participants viewed a set of magic trick videos with the task of finding out how each trick worked, and rated six action verbs for each trick (including one that implied the correct solution) multiple times during solution. They were also asked to indicate the extent to which they experienced an Aha! moment. Patterns of ratings that showed a sudden change towards a correct solution led to stronger Aha! experiences than patterns that showed a more incremental change towards a correct solution, or a change towards incorrect solutions. The results show a connection between sudden changes in problem representations (leading to correct solutions) and the subjective appraisal of solutions as an Aha! experience. This offers the first empirical support for a close relationship between two theoretical constructs that have traditionally been assumed to be related to insightful problem solving.